Routine blood tests as an active surveillance to monitor COVID-19 prevalence. A retrospective study. - Ferrari, Davide; Cabitza, Federico; Carobene, Anna; Locatelli, Massimo (Acta Biomedica Atenei Parmensis, 2020)
Background: In Italy, one of the country most affected by the COVID-19 pandemic, the first autochthonous case appeared in Lombardy on February 20th, 2020. One month later, the number of -COVID-19 patients in Lombardy exceeded 17000 and about 3500 had died. Because of this rapid increase in infected people scientists wonder whether SARS-CoV-2 was already highly circulating in Lombardy before such date. Plasma levels of aspartate aminotransferase (AST) and lactate dehydrogenase (LDH) were shown to be -highly increased in COVID-19 patients. Monitoring their levels in Emergency Room patients during the months preceding February 20th, 2020, might shade light on the prevalence of the disease in the pre-COVID-19 period. Methods: We retrospectively analyzed the AST and LDH levels from more than 30.000 patients admitted to the San Raffaele Hospital Emergency Room (ER) between September 2019 and May 2020 as well as between September 2018 and May 2019. The number of patients diagnosed with respiratory tract diseases were also analyzed. Results: Data showed that the ER averaged AST and LDH levels are highly sensitive to the presence of COVID-19 patients. During, the months preceding February 20th, 2020, AST and LDH levels, as well as the number of patients diagnosed with respiratory tract diseases were similar to their 2019 counterparts. Conclusions: No significant evidence showing that a large number of COVID-19 patients were admitted to the San Raffaele Hospital ER before February 20th, 2020, was found. Thus, the virus was likely circulating, within the Hospital catchment area, either in low amounts or through asymptomatic individuals. Because of the high LDH and AST levels’ variations induced by COVID-19, routine blood tests might be exploited as a surveillance indicator for a possible second wave.